SIKAP PETANI TERHADAP KEBERLANJUTAN USAHA TANI PADI DI WILAYAH PERI URBAN KABUPATEN SLEMAN - Muhamad Imanuddin (FP AGRI 16 UMY 030, 2016)
THE ATTITUDE OF FARMERS TOWARDS THE SUSTAINABILITY OF RICE FARMING IN SUB URBAN AREA OF SLEMAN REGENCY. This research aims to know the level of knowledge of farmers about government regulations on the protection of agricultural land sustainable food and knowing the factors that influence the attitude of farmers towards the sustainability of rice farming. The location is determined by purposive method in six villages which belong to sub urban area of sleman regency. Thirty farmers are chosen as respondents using simple random sampling technique. This research is using the descriptive analysis as the basic method and logistic regression to analyze the factors that influence the attitude of farmers towards the sustainability of rice farming. Primary data obtained through interview by using questionnaire and observation personally. The result showed that knowledge of farmers about government regulations on the protection of agricultural land sustainable food is still very low. Logistic regression analysis shows age, farming experience, farming income, dummy availability of credit and dummy land status significantly influence the attitude of farmers toward the sustainability of rice farming in the alpha 10 percent. On the average, the opportunity of the sustainable farming for farmer in sub urban area of sleman regency is amounted to 53.33 percent.